A Comparison of Muscle Activity Between the Cambered and Standard Bar During the Bench Press Exercise - Krzysztofik, Michal; Golas, Artur; Wilk, Michal; Stastny, Petr; Lockie, Robert George; Zajac, Adam (Frontiers in Physiology, 2020)
The aim of this study was to compare the electromyographic activity between the standard and cambered bar during the bench press (BP) exercise. Twelve resistance-trained males performed the flat BP with a standard and a cambered bar at selected loads (50%, 70%, and 90% 1RM). Muscle activation assessed by surface electromyography (sEMG) was recorded for the pectoralis major, anterior deltoid, and the lateral and long heads of the triceps brachii during each attempt. A three-way repeated measures ANOVA indicated statistically significant main interaction for bar × load × muscle (p < 0.01); bar × load (p < 0.01); bar × muscle (p < 0.01); load × muscle (p < 0.01). There was also a main effect for the bar (p < 0.01); load (p < 0.01); and muscle group (p < 0.01). The post hoc analysis for the main multiple interaction effect of bar × load × muscle showed a statistically significant increase in sEMG for the standard bar in the pectoralis major compared to the cambered bar at 50% 1RM (p < 0.01) and 90% 1RM (p < 0.01), as well as in the triceps brachii long at 90% 1RM (p < 0.01). Furthermore, a statistically significant decrease in sEMG was registered for the standard bar in the anterior deltoid compared to the cambered bar at 90% 1RM (p = 0.02). The results indicated that the cambered bar was superior in activating the anterior deltoid muscle compared to the standard bar during the BP exercise, whereas the standard bar provided higher pectoralis major and triceps brachii long head sEMG activity at 90% 1RM.